2010
DOI: 10.1155/2010/945053
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Lipids and Adipocyte Hormones in Female-to-Male Transsexuals

Abstract: Testosterone therapy in men and women results in decreased high-density lipoprotein cholesterol (HDL) and increased low-density lipoprotein cholesterol (LDL). We sought to determine whether testosterone therapy has this same effect on lipid parameters and adipocyte hormones in female-to-male (FTM) transsexuals. Twelve FTM transsexuals provided a fasting lipid profile including serum total cholesterol, HDL, LDL, and triglycerides prior to and after 1 year of testosterone therapy (testosterone enanthate or cypio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…Triglycerides (TG), total cholesterol, high-density lipoprotein (HDL), and lowdensity lipoprotein (LDL) were measured before and after testosterone therapy began in order to compare changes. Statistically significant decreases in mean HDL were observed in five of the seven studies that reported HDL levels (Chandra et al, 2010;Elamin et al, 2010;Gooren & Giltay, 2008;Ott et al, 2011;. Mean TG elevations were reported in four studies (Elamin et al, 2010;Ott et al, 2011;Gooren & Giltay, 2008); while Chandra et al found that TGs as well as total cholesterol and LDLs remained unchanged.…”
Section: Comparison Of Literaturementioning
confidence: 91%
See 4 more Smart Citations
“…Triglycerides (TG), total cholesterol, high-density lipoprotein (HDL), and lowdensity lipoprotein (LDL) were measured before and after testosterone therapy began in order to compare changes. Statistically significant decreases in mean HDL were observed in five of the seven studies that reported HDL levels (Chandra et al, 2010;Elamin et al, 2010;Gooren & Giltay, 2008;Ott et al, 2011;. Mean TG elevations were reported in four studies (Elamin et al, 2010;Ott et al, 2011;Gooren & Giltay, 2008); while Chandra et al found that TGs as well as total cholesterol and LDLs remained unchanged.…”
Section: Comparison Of Literaturementioning
confidence: 91%
“…All of the articles referred to cohort studies that included FtM patients receiving long-term testosterone therapy (Asscheman et al, 2011;Chandra et al, 2010;Elamin et al, 2010;Gooren & Giltay, 2008;Ott, Aust, Promberger, Huber, & Kaufmann, 2011;Wierckx et al, 2012). Follow-up after testosterone therapy was maintained for at least 1 year later in seven of the eight articles reviewed (Asscheman et al, 2011;Chandra et al, 2010;Gooren & Giltay, 2008;Jacobeit, Gooren, & Schulte, 2009, Ott et al, 2011Wierckx et al, 2012).…”
Section: Comparison Of Literaturementioning
confidence: 99%
See 3 more Smart Citations